Digital Disconnect: Navigating leadership in hybrid work environments: A case study exploring leadership challenges in remote and hybrid teams within project-based organisations - Byström, Ellie; Nivemark, Matilda (My University, 2025)
Remote or hybrid work has become increasingly popular in recent years, mainly driven by the impact of the global COVID-19 pandemic and technical advancements. The construction industry, traditionally reliant on physical presence, is among the sectors significantly affected by this shift. This poses new challenges for leadership, particularly in areas such as communication, motivation, and conflict resolution. This study investigates how such challenges manifest in a large, project-based construction organisation and explores how leadership can adapt to mitigate them. A specific focus has been put on how certain complex challenges emerge in a hybrid work environment. Feedback practices, performance monitoring, and conflict resolution were identified as examples of these that were particularly relevant to this research. The research conducted in this thesis is based on a mixed-method approach, consistent of a case study at a Scandinavian construction company that included 23 semi-structured interviews and a survey with 45 respondents. The findings underscore the importance of setting clear expectations, maintaining consistent and transparent communication, and establishing boundaries to ensure effective leadership in remote or hybrid settings. Many of the participant emphasise the continued need for social interaction and trusting relationships, in spite of the physical distances. Both for continued engagement in teams and for overall wellbeing and a functioning work-life balance. The study concludes that successful remote leadership demands a conscious, flexible approach that is supported by digital tools, regular routines, and individualised strategies. Finally, some practical recommendations are presented, based on participant input and literature findings, to support leadership development in project-based organisations, working in a hybrid environment.
Keywords: eadership, remote work, hybrid work, project-based organisation, construction